2020
DOI: 10.1097/wad.0000000000000381
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-synuclein Levels in the Differential Diagnosis of Lewy Bodies Dementia and Other Neurodegenerative Disorders

Abstract: Subjectives: Lewy body dementia (LBD) is the second most common type of neurodegenerative dementia after Alzheimer disease (AD). It is characterized by the accumulation of Lewy bodies and Lewy neurites which are composed of aggregated phosphorylated alpha-synuclein, which is a presynaptic neuronal protein genetically and neuropathologically linked to Parkinson disease and to LBD. Alpha-synuclein is thought to contribute to LBD pathogenesis and to linked to disruption of cellular homeostasis and neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“… 18 The presence of proteins with a pathological structure results in the activation of glial cells in the brain (astroglial and microglial), triggering inflammatory processes, as free oxygen radicals, excitatory amino acids, interleukins, as well as nitric oxide are released. 1 , 18 Additionally, these compounds contribute to the death of neurons and their connections. 1 , 18 Furthermore, there is a loss of cholinergic neurons in the forebrain, there are also changes in the synapses of the cerebral cortex and hippocampus.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“… 18 The presence of proteins with a pathological structure results in the activation of glial cells in the brain (astroglial and microglial), triggering inflammatory processes, as free oxygen radicals, excitatory amino acids, interleukins, as well as nitric oxide are released. 1 , 18 Additionally, these compounds contribute to the death of neurons and their connections. 1 , 18 Furthermore, there is a loss of cholinergic neurons in the forebrain, there are also changes in the synapses of the cerebral cortex and hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 18 Additionally, these compounds contribute to the death of neurons and their connections. 1 , 18 Furthermore, there is a loss of cholinergic neurons in the forebrain, there are also changes in the synapses of the cerebral cortex and hippocampus. 1 , 18 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study showed CSF cytokine/chemokine/growth factor profiles in MSA-C and SCA in which pro-inflammatory cytokines like IL-6, GM-CSF, and MCP-1 displayed specific correlation with the disease stage in MSA-C (Yamasaki et al, 2017). Besides, several proteins including calbindin D, amyloid precursor protein (APP), S100B, and synuclein-alpha (α-synuclein) have been ascertained in neurodegenerative diseases such as AD, Huntington's disease (HD), multiple sclerosis, and MSA (Steiner et al, 2011;Stefanits et al, 2014;van Waalwijk van Doorn et al, 2016;Mavroudis et al, 2020). Meanwhile, the investigation of other proteins such as carbonic anhydrase, CD117/c-kit, proganulin, and kallikreins which may play roles in neural circuit development and maintenance, stress response, innate immunity, and aging as well as brain innate immunity may open a new avenue for the study of MSA (Greco et al, 2012;Dukic et al, 2016;Chitramuthu et al, 2017;Gennarini et al, 2017;Hsieh et al, 2019).…”
Section: Introductionmentioning
confidence: 99%